Design and analysis of building evacuation system's controller using FPGA / Nurul Fatihah Jusoh, Sukreen Hana Herman and Suhana Sulaiman - Jusoh, Nurul Fatihah; Herman, Sukreen Hana; Sulaiman, Suhana (UiTM Press, 2018)
This work is focused on the hardware support for improving an emergency evacuation known as decision support system, "op_sys". The Controller Operating System Unit is a module in "op_sys" that is designed to improve occupants' information if there is an emergency situation such as fires is occured. This module is handled through Controller Alarm and Controller System Floor, by displaying the data output through FPGA board on three varieties of manually selected modes at FPGA board. Also, the Controller System Floor is tested for simulation waveform using Modelsim Altera EDA application software. The compilation for hardware verification functionality, simulation waveform functionality, and timing analysis show the results is consistent and met the specification requirement with the theoretical analysis. Furthermore, the estimated of four alarm sensors and controller system floor is required if the system is implemented for the future work.